Correction: Sulfate activation of wheat straw ash to enhance the properties of high-performance concrete with recycled aggregates and waste tire steel fibers. - Fadi Althoey; Osama Zaid; Khaled Mohamed Elhadi (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0311838.].